2014
DOI: 10.1007/s10072-013-1611-6
|View full text |Cite
|
Sign up to set email alerts
|

Addiction and empathy: a preliminary analysis

Abstract: Addicted patients show impaired social functioning. Chronic drug consumption may lead to impairments in decoding empathic cues. The aim of the study is to explore empathy abilities in addicted patients and the hypothesis of a differential impairment between affective and cognitive empathy. 62 addicted patients and 40 healthy volunteers were evaluated using the empathy quotient (EQ) and its subscales cognitive empathy (factor 1), emotional empathy (factor 2), social skills (factor 3). Patients scored statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
4
34
0
2
Order By: Relevance
“…Indeed, some tasks were purely focused on cognitive ToM (e.g., False‐Beliefs task [Maurage et al., ]; Versailles‐Situational Intention Reading [Nandrino et al., ]), while others presented affective and cognitive items but regrouped them into a global score (Bosco et al., ; Thoma et al., ). However, this distinction between affective and cognitive ToM is of crucial interest in alcohol dependence, as earlier results in this population have shown (i) a specific deficit for emotional empathy (with conversely preserved cognitive empathy), these abilities being strongly related to ToM (Ferrari et al., ; Maurage et al., ); and (ii) a marked deficit for emotional ToM in the “Reading the Mind in the Eyes” test (Baron‐Cohen et al., ), with, conversely, a preserved processing of nonemotional mental states (Maurage et al., ; Nandrino et al., ). These results suggest that alcohol dependence may not be related to a global ToM impairment as reported earlier, but rather to a dissociation between affective and cognitive subcomponents.…”
mentioning
confidence: 96%
“…Indeed, some tasks were purely focused on cognitive ToM (e.g., False‐Beliefs task [Maurage et al., ]; Versailles‐Situational Intention Reading [Nandrino et al., ]), while others presented affective and cognitive items but regrouped them into a global score (Bosco et al., ; Thoma et al., ). However, this distinction between affective and cognitive ToM is of crucial interest in alcohol dependence, as earlier results in this population have shown (i) a specific deficit for emotional empathy (with conversely preserved cognitive empathy), these abilities being strongly related to ToM (Ferrari et al., ; Maurage et al., ); and (ii) a marked deficit for emotional ToM in the “Reading the Mind in the Eyes” test (Baron‐Cohen et al., ), with, conversely, a preserved processing of nonemotional mental states (Maurage et al., ; Nandrino et al., ). These results suggest that alcohol dependence may not be related to a global ToM impairment as reported earlier, but rather to a dissociation between affective and cognitive subcomponents.…”
mentioning
confidence: 96%
“…One study showed that ADI and CI reported similar emotional responses (i.e., from very negative to very positive) to the facial expressions of basic emotions (Dethier and Blairy, ), thus suggesting that ADI and CI do not differ regarding the valence of their emotional responses to others’ emotional states. Moreover, using self‐evaluative questionnaires, previous studies (Amenta et al., ; Ferrari et al., ; Maurage et al., ; Thoma et al., ) revealed contradictory findings concerning the compassion and personal distress of ADI in response to others’ misfortune (i.e., either lower than or similar to CI). Thus, only a few studies have examined the emotional responses of ADI to others’ states and have used only self‐evaluative reports, which are known to be highly biased by self‐perception.…”
mentioning
confidence: 96%
“…This confirmed that the affective deficit extends beyond basic emotional states. Other studies have described, on the basis of questionnaires or experimental tasks, deficits in a wide range of emotional abilities such as empathy,30,31 alexithymia,32 or irony detection,33 leading to the proposal of a wide affective processing deficit in ADI.…”
Section: Beyond Efe Recognition: Affective Abilities and Social Cognimentioning
confidence: 99%